2018
DOI: 10.1038/s41598-018-32303-7
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of melanogenesis by Nymphaea nouchali (Burm. f) flower extract through the regulation of cAMP/CREB/MAPKs/MITF and proteasomal degradation of tyrosinase

Abstract: Medicinal plants have been used to treat diseases from time immemorial. We aimed to examine the efficacy of the ethyl acetate fraction of Nymphaea nouchali flower extract (NNFE) against melanogenesis process, and the underlying mechanisms in vitro and in vivo. Paper spray ionisation mass spectroscopy and (+) mode electrospray ionisation revealed the presence of seven flavonoids, two spermidine alkaloids, 3,4,8,9,10-pentahydroxy-dibenzo[b,d]pyran-6-one, and shoyuflavone C in NNFE. NNFE (100 µg/mL) significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 45 publications
3
36
0
Order By: Relevance
“…A number of reports have demonstrated the activation of p38 pathway induces MITF expression and contributes to pigmentation . However, Bellei et al reported that p38 suppress pigmentation through proteasomal degradation of tyrosinase . In our current research, we demonstrated that ISL inhibited melanogenesis and melanosome transport mainly via EKR‐mediated MITF degradation.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…A number of reports have demonstrated the activation of p38 pathway induces MITF expression and contributes to pigmentation . However, Bellei et al reported that p38 suppress pigmentation through proteasomal degradation of tyrosinase . In our current research, we demonstrated that ISL inhibited melanogenesis and melanosome transport mainly via EKR‐mediated MITF degradation.…”
Section: Discussionsupporting
confidence: 51%
“…On one hand, several reports have demonstrated the activation of p38 pathway induces MITF expression and contributes to pigmentation . On the other hand, p38 was found to suppress pigmentation via proteasomal degradation of tyrosinase …”
Section: Introductionmentioning
confidence: 99%
“…Melanin content in the mouse cells was measured following the methodology of a previous study [39], with slight modifications. Mouse melanoma B16 4A5 cells were seeded in a six-well plate (6.7 × 10 3 cells/cm 2 ) and cultured for 24 h in the complete medium.…”
Section: In Vitro Pigmentation Assaymentioning
confidence: 99%
“…For example, Slominski et al reported melanogenesis regulated HIF-1α and HIF-1α-regulated target genes are involved in angiogenesis and cellular metabolism [ 76 ]. Similarly, the involvement of cyclic adenosine monophosphate (cAMP) and response binding protein element (CREB) in MITF activation and subsequent upregulation of melanogenesis-regulated gene coding for tyrosinase has been reported [ 77 , 78 ]. Since our study showed a link between HuR and MITF and that HuR is known to regulate HIF-1α and HIF-1α-regulated target genes such as VEGF, it will be of interest to investigate the role of HuR in melanogenesis and melanogenesis regulated tyrosinase in melanoma.…”
Section: Discussionmentioning
confidence: 99%